Sustainable Sand Mining Management in Merapi Area Using Groundsills - Jazaul Ikhsan, masaharu Fujita, Hiroshi takebayashi (Kyoto University, 2009)
Mt. Merapi is one of the most active volcanoes in the world and located at 30 km north-northeast from yogyakarta, indonesia. in this study, we discussed the basic management concepts of sand mining and groundsill installation for such sustainable sediment management.